Analysis of chosen polymorphisms rs2476601 a/G – PTPN22, rs1990760 C/T – IFIH1, rs179247 a/G – TSHR in pathogenesis of autoimmune thyroid diseases in children. (19th May 2018) - Rydzewska, Marta; Góralczyk, Aleksandra; Gościk, Joanna; Wawrusiewicz-Kurylonek, Natalia; Bossowska, Anna; Krętowski, Adam; Bossowski, Artur
Abstract: Background: Autoimmune thyroid diseases are multifactorial diseases with a genetic susceptibility and environmental factors. A potential role of the protein tyrosine phosphatase non-receptor type 22 (PTPN22) gene, the interferon-induced helicase domain 1 (IFIH1) gene, the thyroid-stimulating hormone receptor (TSHR) gene polymorphisms on autoimmune thyroid diseases (AITDs) in adults has been established unequivocally, but there is still lack of research articles including group of children. Objective and hypotheses: To estimate the association of polymorphisms of PTPN22, IFIH1 and TSH-R genes with the pre-disposition to Graves' disease (GD) and Hashimoto's thyroiditis (HT) in children. Methods: The study was performed in 142 patients with GD, 57 with HT and 160 healthy volunteers. The three single-nucleotide polymorphisms (SNPs): rs2476601 – PTPN22, rs1990760 – IFIH1 and rs179247 – TSHR were genotyped by TaqMan SNP genotyping assay using the real-time PCR. Results: Rs2476601 A alleles were more frequent in patients with GD in comparison to healthy subjects ( p = .009 with odds ratio [OR] = 2.13). Rs2476601 A alleles were more frequent in patients with HT in comparison to healthy subjects ( p = .008, OR = 2.48). Rs1990760 T alleles were more frequent in male patients with GD in comparison to healthy males ( p = .003, OR = 3.00). In case of HT patients, rs1990760 T alleles were also more frequent in males compared to healthy subjects ( p = .086, OR =2.47). Rs179247 A alleles were more frequent in patients with GD in comparison to healthy subjects ( p = 0.039, OR = 1.51). Conclusions: Rs2476601 A/G, Rs1990760 C/T and Rs179247 A/G polymorphisms could contribute to the development of AITDs in children. The main risk factor for rs2476601 and rs179247 is allele A. In case of rs1990760, the main risk factor is allele T.